Impelementasi Kebijakan Analisis Jabatan dan Beban Kerja pada Biro Organisasi Sekretariat Daerah Provinsi Sulawesi Tengah - Erland, Nuraini Arshy; Daswati, Daswati; Asrifai, Asrifai (CV. Rayyan Dwi Bharata, 2026)
This research aims to examine the implementation of the Minister of Administrative and Bureaucratic Reform Regulation No. 1 of 2020 at the Organization Bureau of the Regional Secretariat of Central Sulawesi Province. The theory used in this study is Edward III’s (2003:11) theory, which consists of four criteria: communication, resources, disposition, and bureaucratic structure. The research method applied is descriptive qualitative. Data were collected through observation, documentation, and interviews. Informants were selected using purposive sampling, involving five individuals considered to have in-depth knowledge regarding the research issues. The data analysis techniques included data collection, data condensation, data display, and conclusion drawing/verification. The results showed that the implementation of Job Analysis (Anjab) and Workload Analysis (ABK) has not been optimal. This is evident from the excess number of P3K positions in 2023 caused by several factors, including application errors and a lack of coordination among related stakeholders, resulting in proposed formations exceeding the actual needs. Since P3K employees cannot be transferred to other units, this surplus has led to ineffective human resource distribution. Furthermore, before 2022, tasks related to Anjab and ABK, which should have been the responsibility of the Administrative Unit, were instead carried out by the technical team, thus hindering effective and efficient implementation of Anjab and ABK.